HLA alleles as biomarkers of high-titre neutralising antibodies to interferon-β therapy in multiple sclerosis. Issue 6 (19th April 2014) - Núñez, Concepción; Cénit, Mª Carmen; Alvarez-Lafuente, Roberto; Río, Jordi; Fernández-Arquero, Miguel; Arroyo, Rafael; Montalbán, Xavier; Fernández, Oscar; Oliver-Martos, Begoña; Leyva, Laura; Comabella, Manuel; Urcelay, Elena
Abstract : Background: Recombinant interferon β (IFNβ) is a first-line therapy for relapsing-remitting multiple sclerosis (MS), with a proven effect on the inflammatory activity. Neutralising antibodies against IFNβ (NAbs) promote a loss of IFNβ bioactivity in a titre-dependent way and their development was associated with certain human leucocyte antigen (HLA) alleles. We investigated the contribution conferred by HLA alleles on the development of NAbs in independent cohorts of Southern Europe. Methods: Serum NAbs from 610 MS patients with HLA-genotype data were evaluated by cytopathic effect assay: negative tests included at least one negative result (NAb titres<20 NU/mL) after 1 year treatment; NAb-titres ≥20 NU/mL were positive tests and NAb titres ≥150 NU/mL in any test were classified as high-titre positives. Results: The combined presence of DRB1*07/DQA1* 02 with A *26 or B*14 was found in 20% of patients with NAbs at high titres, but only in 5.4% of NAb-negative patients (p=0.00052, OR (95% CI) 4.34 (1.85 to 10.13)). The DRB1*04:01 allele was also more frequently carried by patients with high titres of NAbs (10% vs 4.5%; p=0.046, OR (95% CI) 2.38 (0.93 to 5.92)). The alleles carried at a significantly lower frequency in patients with high persistent NAbs corresponded to the A*11 allele (3.3% vs 13.8%; p=0.023, OR (95% CI) 0.22 (0.02 to 0.87)), as well as the DRB1*03/DQA1*05/DQB1*02 haplotype (16.3% vs 26.8%; p=0.02, OR (95% CI) 0.53 (0.27 to 1.03)) and the DRB1*13/DQA1*01:03/DQB1*06:03 haplotype (2.5% vs 9.1%; p=0.045, OR (95% CI) 0.25 (0.03 to 1.02)). Conclusions: 50% of the studied MS patients carried some of the five independently associated HLA allele/allele combinations described in this work. This relevant percentage of patients could benefit a therapeutic decision.